2022
DOI: 10.1007/s11524-021-00589-0
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Rollouts and the Reproduction of Urban Spatial Inequality: Disparities Within Large US Cities in March and April 2021 by Racial/Ethnic and Socioeconomic Composition

Abstract: Rollouts of COVID-19 vaccines in the USA were opportunities to redress disparities that surfaced during the pandemic. Initial eligibility criteria, however, neglected geographic, racial/ethnic, and socioeconomic considerations. Marginalized populations may have faced barriers to then-scarce vaccines, reinforcing disparities. Inequalities may have subsided as eligibility expanded. Using spatial modeling, we investigate how strongly local vaccination levels were associated with socioeconomic and racial/ethnic co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 146 publications
(131 reference statements)
2
19
0
1
Order By: Relevance
“…While existing studies have shown that concentration of racial minorities is associated with lower levels of vaccine uptake especially during early rollout when the supply of COVID-19 vaccines was limited ( McFadden et al, 2021 ; Nguyen et al, 2022 ; DiRago 2022 ), this study helps advance current knowledge in several major ways. First, I have shown that concentrations of racial minorities are not always associated with lower COVID-19 vaccine uptake.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…While existing studies have shown that concentration of racial minorities is associated with lower levels of vaccine uptake especially during early rollout when the supply of COVID-19 vaccines was limited ( McFadden et al, 2021 ; Nguyen et al, 2022 ; DiRago 2022 ), this study helps advance current knowledge in several major ways. First, I have shown that concentrations of racial minorities are not always associated with lower COVID-19 vaccine uptake.…”
Section: Discussionmentioning
confidence: 94%
“…These disadvantaged communities are less resilient in their ability to respond to and recover from the waves of the pandemic because they are in short supply of vital resources to contend with the spread of the virus such as sanitizers, masks, as well as testing facilities and health care resources ( Godoy & Wood, 2020 ; Gaynor & Wilson, 2020 ). These communities also show lower COVID-19 vaccination rates ( DiRago, Li, et al, 2022 ; Hughes et al, 2021 ; Khubchandani & Macias, 2021 ; McFadden et al, 2021 ), and this exacerbates the unequal impacts of the pandemic. In Maryland, for example, Cardona et al (2021) show that counties with higher concentrations of Blacks and Latinos have higher infection, morbidity and mortality from COVID-19, but lower vaccination rates as compared to counties with predominantly Whites.…”
Section: Racial Concentration and Covid-19 Vaccinationmentioning
confidence: 99%
See 3 more Smart Citations